Análises isoenzimáticas, moleculares e ultraestruturais em camarões dulcícolas do gênero Macrobrachium - Lopes, Alessandro Garcia [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Prawns of the genus Macrobrachium (Crustacea, Decapoda, Palaemonidae) can be found in freshwater environments, widely distributed throughout tropical and subtropical regions of the world, including regions near the coast. Some species of this genus, for example Macrobrachium rosenbergii, present economic value, which are reared and traded as food. In the northwest region of São Paulo State two exotic freshwater prawn species are found, classified as M. amazonicum and M. jelskii, which were recently introduced to the aquatic reservoirs of hydroelectric power plants and then, disseminated throughout reservoirs in this region of the State. These species have cryptic and overnight habits, being predators of fish larvae and also being prey to adult fishes and other organisms. M. amazonicum and M. jelskii present high rates of interspecific similarity in terms of morphological characters, which are generally used to distinguish them, what may induce mistakes in taxonomic identification. The objective of this study was to conduct morphometric, ultrastructural, isoenzymatic and molecular analyses of M. amazonicum and M. jelskii, in order to obtain more data about their differentiation. The prawns were collected in reservoirs of Sales/SP and Mendonça/SP. Morphometric analyses were performed involving the structures of telsons, internal caudal spines and rostrums. Scanning electron microscopy analyses were performed on structures of telsons, internal caudal spines and male appendices. Isoenzymatic analyses by polyacrylamide gel electrophoresis included the enzymes alcohol dehydrogenase, octanol dehydrogenase, glucose-6-phophate dehydrogenase, lactate dehydrogenase, amylase and esterases of hepatopancreas and muscle tissue. Molecular analyses were performed by amplification and sequencing of ITS-1(Internal Transcribed Spacer 1) intergenic spacer from rDNA. The amplificated fragments were used for analyzing length polymorphism restriction fragments ...

Os camarões do gênero Macrobrachium (Crustacea, Decapoda, Palaemonidae), encontrados em ambientes de água doce, são amplamente distribuídos pelas regiões tropicais e subtropicais do mundo, inclusive em locais próximos ao litoral. Algumas espécies desse gênero, como por exemplo M. rosenbergii, apresentam valor econômico, sendo cultivadas e comercializadas como alimento. Na região Noroeste do Estado de São Paulo, são encontradas as espécies classificadas como M. amazonicum e M. jelskii, as quais são espécies exóticas de camarões dulcícolas recentemente introduzidas e amplamente disseminadas em reservatórios de usinas hidrelétricas desta região. Essas espécies possuem hábitos crípticos e noturnos, sendo predadores de larvas de peixes e também presas de peixes adultos e outros organismos. M. amazonicum e M. jelskii apresentam grande similaridade interespecífica em termos de caracteres morfológicos, o que pode dificultar a classificação taxonômica desses organismos. O objetivo deste estudo foi conduzir análises morfométricas, ultraestruturais, isoenzimáticas e moleculares em M. amazonicum e M. jelskii, na tentativa de obter-se novos dados para distinguí-los. Os camarões foram coletados das populações dos reservatórios de Sales/SP e Mendonça/SP. As análises morfométricas englobaram as medidas do télson, dos espinhos caudais internos e do rostro. As análises por microscopia eletrônica de varredura foram realizadas nas estruturas do télson, nos espinhos caudais internos e no apêndice masculino. As análises isoenzimáticas, realizadas por eletroforese em gel de poliacrilamida, abrangeram as enzimas álcool desidrogenase, octanol desidrogenase, glicose-6-fosfato desidrogenase, lactato desidrogenase, amilase e esterases do hepatopâncreas e tecido muscular. Análises moleculares envolveram a amplificação do espaçador intergênico interno ITS-1 (Internal Transcribed Spacer 1) do rDNA. Os fragmentos ...
Keywords: Genetica animal; Camarão de agua doce; Macrobrachium; Isoenzimas; Bioinvasão; Crayfish